MONETARY–FISCAL INTERACTION AND PUBLIC DEBT IN THE EUROPEAN UNION UNDER CONDITIONS OF THE GLOBAL ECONOMIC CRISIS - Irena Milojević; Milovan Rosić (Finansijski savetnik, 2026)
The paper analyzes the relationship between monetary and fiscal policy in the European Union, with particular focus on the public debt crisis in member states in the context of the global economic crisis of 2008. The introduction of the common euro currency contributed to deeper economic integration, lower transaction costs, and easier access to capital, but at the same time created a structural asymmetry between centralized monetary policy and decentralized fiscal policies of the member states. This mismatch allowed public debt to grow in some countries, particularly Greece, Portugal, Spain, Ireland, and Italy. The global financial crisis of 2008 exposed the weaknesses of this institutional framework, leading to disruptions in credit flows, problems with debt refinancing, and the need for interventions by the European Union and international financial institutions. Fiscal consolidation measures and financial assistance temporarily stabilized the situation, but at the same time pointed to the long-term problem of insufficient fiscal coordination within the Eurozone. The paper concludes that the long-term stability of the common currency requires better coordination between monetary and fiscal policy, with the establishment of a fiscal union at the European Union level highlighted as a potential solution.